Comparative evaluation of respiratory-gated and ungated FDG-PET for target volume definition in radiotherapy treatment planning for pancreatic cancer. Issue 2 (August 2016) - Kishi, Takahiro; Matsuo, Yukinori; Nakamura, Akira; Nakamoto, Yuji; Itasaka, Satoshi; Mizowaki, Takashi; Togashi, Kaori; Hiraoka, Masahiro
Abstract: Objective: The purpose of this study was to evaluate the usefulness of respiratory-gated positron emission tomography (4D-PET) in pancreatic cancer radiotherapy treatment planning (RTTP). Materials and methods: Fourteen patients with 18F-fluorodeoxyglucose (FDG)-avid pancreatic tumours were evaluated between December 2013 and March 2015. Two sets of volumes were contoured for the pancreatic tumour of each patient. The biological target volume in three-dimensional RTTP (BTV3D) was contoured using conventional respiratory un-gated PET. The BTV3D was then expanded using population-based margins to generate a series of internal target volume 3D (ITV3D) values. The ITV 4D (ITV4D) was contoured using 4D-PET. Each of the five phases of 4D-PET was used for 4D contouring, and the ITV4D was constructed by summing the volumes defined on the five individual 4D-PET images. The relative volumes and normalized volumetric overlap were computed between ITV3D and ITV4D. Results: On average, the FDG-avid tumour volumes were 1.6 (range: 0.8–2.3) fold greater in the ITV4D than in the BTV3D. On average, the ITV3D values were 2.0 (range: 1.1–3.4) fold larger than the corresponding ITV4D values. Conclusion: The ITV generated from 4D-PET can be used to improve the accuracy or reduce normal tissue irradiation compared with conventional un-gated PET-based ITV.